Tissue Is More Important than Time in Stroke Patients Being Assessed for Thrombolysis - Bivard, Andrew; Spratt, Neil; Miteff, Ferdinand; Levi, Christopher; Parsons, Mark William (Frontiers in Neurology, 2018)
Aim: The relative prognostic importance of modern imaging profiles compared to standard clinical characteristics is uncertain in acute stroke patients. In this study we aimed to compare baseline multimodal CT imaging measures with known clinical predictors of patient outcome at 3 months (modified Rankin Scale, mRS). Methods: We collected baseline, 24 hour, and day 90 clinical and imaging data from acute ischemic stroke patients being assessed for thrombolytic therapy between 2010 and 2015 at a single centre as part of a retrospective analysis. Results: 561 patients presenting within 4.5 hours of ischemic stroke onset who were eligible for thrombolysis based on standard clinical criteria were assessed. Acute infarct core volume on CTP was the strongest univariate predictor of patient outcome (mRS 0-2 R2 0.497, p<0.001), followed by collateral grade (mRS 0-2 R2 0.281, p<0.001). The strongest baseline clinical predictor of outcome was NIHSS (mRS 0-2, R2 = 0.203, p<0.001). Time to treatment (mRS 0-2 R2 0.096, p=0.01) and age (mRS 0-2 R2 0.027, p=0.013) were relatively weak univariate baseline clinical predictors of 3 month outcome. In multivariate analysis, acute infarct core volume and collateral grade were the only significant baseline predictors of 3-month disability (both p<0.001). Conclusion: In patients assessed for thrombolysis by combined clinical and multimodal CT criteria within 4.5 hours of onset, the size of the CTP infarct core and collateral grade on multimodal CT were highly predictive of patient outcome. Standard clinical variables, including time to treatment and NIHSS, were not as strongly predictive as multimodal CT variables.